Comparison of laboratory and field bioassays of laboratory‐reared Cydia pomonella (Lepidoptera: Tortricidae) quality and field performance. (21st January 2013) - Carpenter, J. E.; Blomefield, T.; Hight, S. D.
Abstract: Maximum production and fitness of insect species that are mass‐reared for biological control programmes such as the sterile insect technique (SIT) have benefitted from the employment of quality control and quality management. With a growing interest in the use of SIT as a tactic for the suppression/eradication of key lepidopteran pests, such as the codling moth, Cydia pomonella L. (Lepidoptera: Tortricidae), there is a parallel interest in inexpensive bioassays that can accurately detect differences in insect quality and monitor insect field performance. In this study, we examined laboratory (mating and flight ability) bioassays and field (field cage and open field release) bioassays simultaneously to discern the ability of the different bioassays to predict quality and field performance of codling moths produced in a commercial mass‐rearing facility. Moth quality was degraded by different levels of radiation during the sterilization procedure. Both the laboratory flight bioassay and the field cage bioassay successfully detected quality and performance differences that were relevant to moth performance in the field. However, the study data suggest that the field cage bioassay was a better predictor of the daily performance of males that had been released in the orchard than the laboratory flight bioassay. Conversely, data suggest that the controlled climatic conditions of the laboratory allowed the flight cylinder bioassay to be more sensitive in detecting daily fluctuations in the quality of moths caused by factors within the mass‐rearing facility. Therefore, both laboratory and field bioassays may be required to provide feedback on quality and performance of mass‐reared moths in a SIT programme.